Selenium, but Not Lycopene or Vitamin E, Decreases Growth of Transplantable Dunning R3327-H Rat Prostate Tumors - Lindshield, Brian L.; Ford, Nikki A.; Canene-Adams, Kirstie; Diamond, Alan M.; Wallig, Matthew A.; Erdman, John W. Jr. (My University, 2010)
Background: Lycopene, selenium, and vitamin E are three micronutrients commonly consumed and supplemented by men diagnosed with prostate cancer. However, it is not clear whether consumption of these compounds, alone or in combination, results in improved outcomes. Methodology/Principal Findings: We evaluated the effects of dietary lycopene (250 mg/kg diet), selenium (methylselenocysteine, 1 mg/kg diet), and vitamin E (γ-tocopherol, 200 mg/kg diet) alone and in combination on the growth of androgen-dependent Dunning R3327-H rat prostate adenocarcinomas in male, Copenhagen rats. AIN-93G diets containing these micronutrients were prefed for 4 to 6 weeks prior to tumor implantation by subcutaneous injection. Tumors were allowed to grow for ~18 weeks. Across diet groups, methylselenocysteine consumption decreased final tumor area (P = 0.003), tumor weight (P = 0.003), and the tumor weight/body weight ratio (P = 0.003), but lycopene and γ-tocopherol consumption intake did not alter any of these measures. There were no significant interactions among nutrient combinations on tumor growth. Methylselenocysteine consumption also led to small, but significant decreases in body weight (P = 0.007), food intake (P = 0.012), and body weight gain/food intake ratio (P = 0.022). However, neither body weight nor gain/food intake ratio was correlated with tumor weight. Methylselenocysteine, lycopene, and γ-tocopherol consumed alone and in combination did not alter serum testosterone or dihydrotestosterone concentrations; tumor proliferation or apoptosis rates. In addition, the diets also did not alter tumor or prostate androgen receptor, probasin, selenoprotein 15, selenoprotein P, or selenium binding protein 2 mRNA expression. However, using castration and finasteride-treated tissues from a previous study, we found that androgen ablation altered expression of these selenium-associated proteins. Conclusions: Of the three micronutrients tested, only methylselenocysteine consumption reduced growth of transplantable Dunning R3327-H prostate tumors, albeit through an unresolved mechanism.
Keywords: Selenium; Lycopene; Vitamin E; Prostate cancer; Diet